Cryodamage of plasma membrane and acrosome region in chicken sperm. (17th October 2018) - Olexikova, Lucia; Miranda, Marsia; Kulikova, Barbora; Baláži, Andrej; Chrenek, Peter
Abstract: Sperm plasma membrane is an essential structure of sperm resistance to freezing. Signs of cryodamage can be visible on the sperm plasma membrane. The aim of our study was to evaluate the appearance of plasma membrane and acrosome in fresh and frozen‐thawed chicken sperm using electron and fluorescence microscopy. Semen was collected from 12 sexually mature roosters of Ross PM3 heavy line, diluted with Kobidil + extender with 16% of ethylene glycol (KEG; control) or with KEG in combination with one of following non‐permeating cryoprotectants: trehalose (KEG‐TRE) or glycine (KEG‐GLY). Fluorescence staining was used for detection of the membrane integrity, apoptotic changes and viability (Annexin V, Yo‐PRO‐1, PI, respectively). Ultrathin sections (70 nm) from samples were prepared to examine sperm head ultrastructure. Freezing process significantly worsened the status of the sperm plasma membranes. In all frozen groups, only about a quarter of the evaluated sperm were graded as class I quality. In the KEG and KEG‐GLY groups, about half of sperm had severe plasma membrane damages (III class). In sperm with extensively damaged membranes (III class), the acrosome–sperm head junction was mostly disturbed. The use of trehalose was more beneficial ( p < 0.05) for sperm plasma membrane than the use of glycine. In contrast, a decrease ( p < 0.05) in the apoptotic sperm ratio (Yo‐PRO‐1) was noted in the KEG‐GLY group when compared to other treatments. In conclusion, we identified different plasma membrane and acrosome damages in cryopreserved chicken sperm. The loss of acrosomes can contribute to diminishing of fertilization ability of cryopreserved chicken sperm.